EFEKTIFITAS METODA FGD TERHADAP PERILAKU IBU HAMIL TENTANG ANC DI PUSKESMAS MAUKARO - ANATOLIA KARMELITA DOONDORI (Poltekkes Kemenkes Kupang, 2016)
Introduction: ANC (Antenatal Care) is an examination or supervision of pregnancy to optimize mental and physical health of pregnant women, so as to face childbirth, postpartum, breastfeeding preparation and fair return of reproductive health. Health care is an important component of antenatal care to identify any helath problem as early as possible. The purpose of this study to clarification effect of focus group method to the behavior pregnant women about antenatal care.Method: It’s a quasy experimental research there were 15 respondents taking by purposive sampling. They are pregnant women who visited Puskesmas Maukaro Ende at January until October 2016 who have Commentaries Labor Day on October 2016, and meet some of inclusion criteria. This research use quisionare is instrumental.Result: Based on the result of analysis of FGD method to the respondent behavior about ANC, for knowledge using Wilcoxon Sign Rank Test with significance level α = 0.005 obtained p = 0.015 indicate there is significant influence of FGD method to pregnant woman knowledge about ANC, for attitude significance level α <0,05 got The result p = 0.046 means there is a significant influence FGD method on the attitude of the mother about the ANC while for the action with the level of significance α <0.05 obtained p = 0.013, showed significant influence FGD method on the mother's action about ANC. Conclusion: It can be conclude that FGD Method is effective to improve the behavior of pregnant women which knowledge, attitudes and actions.